ENHANCE THE AQUEOUS SOLUBILITY OF DICLOFENAC THROUGH THE SYNTHESIS OF DICLOFENAC-INOSITOL PRODRUG - Qader, Hemn Latif; alsheikhly, Omar Abdulrahman; Hamadameen Hama, Hewa Abdulla; Qader, Adnan Burhan (Science Journal of University of Zakho, 2024)
Due to limited aqueous solubility, poor bioavailability makes oral dosage formulations difficult to formulate. Chemical alteration of medicinal compounds improves solubility. Prodrug design is a popular molecular modification method that improves solubility and oral bioavailability. This study aims to synthesize a diclofenac prodrug to enhance aqueous solubility. In this study, diclofenac was esterified with inositol to make a prodrug (DIP), which was identified by 1H-NMR and FT-IR. A computational pharmacokinetic software was used to study DIP's pharmacokinetic profile, and saturation solubility was measured in phosphate buffer (pH 6.8) and 0.1 HCl (pH 1.2) solutions. The ester bands of (C=O) stretch at 1739 cm-1 and the elimination of H signals of carboxylic acid at 10-12 ppm in the 1H-NMR spectrum proved the synthesis of (DIP). Diclofenac solubility increased 827-fold in phosphate buffer solution (p < 0.05) from 0.059± 0.0164 mg/ml to 48.8± 0.034 mg/ml, primarily due to polarity change. The solubility of diclofenac and (DIP) in 0.1 N HCl (pH 1.2) was 0.016± 0.0031 and 0.018± 0.002, respectively. The improvement in solubility in the acidic medium was non-significant (p > 0.05) due to acid hydrolysis of the ester bond between inositol and the drug. The synthesis of diclofenac prodrug can greatly enhance its water solubility.